2015
DOI: 10.1002/jmv.24127
|View full text |Cite
|
Sign up to set email alerts
|

Serological evaluation of possible exposure to Ljungan virus and related parechovirus in autoimmune (type 1) diabetes in children

Abstract: Exposure to Ljungan virus (LV) is implicated in the risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…LV has been associated with several human diseases [26,[28][29][30][31], and causes symptoms in laboratory mice [28], but LV has yet to be isolated from humans or proven a causative agent of disease. High seroprevalence (36%, 38%) to LV has recently been detected in humans in Finland [15], indicating a fairly high exposure to LV and/or to an antigenically-related virus in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…LV has been associated with several human diseases [26,[28][29][30][31], and causes symptoms in laboratory mice [28], but LV has yet to be isolated from humans or proven a causative agent of disease. High seroprevalence (36%, 38%) to LV has recently been detected in humans in Finland [15], indicating a fairly high exposure to LV and/or to an antigenically-related virus in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, previous studies on Swedish children and young adults (0–18 years old) indicate that children with newly diagnosed type 1 diabetes had higher levels of LVA than healthy controls, suggesting that LV could possibly contribute to type 1 diabetes in humans [Nilsson et al, , , ]. These studies also implied that LVA levels were higher in young children and that the incidence of type 1 diabetes seemed to co‐vary with subjects with high LVA levels [Nilsson et al, , , ].…”
Section: Introductionmentioning
confidence: 94%
“…The etiology of type 1 diabetes is not clarified but virus infections remain a possible trigger of islet autoimmunity [Tauriainen et al, 2011]. It has previously been suggested that Ljungan virus (LV), which is carried by bank voles (Myodes glareolus) may be associated with type 1 diabetes [Niklasson et al, 2003b;Nilsson et al, 2009Nilsson et al, , 2013Nilsson et al, , 2015. Zoonotic agents have in common that one or more animal species function as a reservoir during at least some part of the life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Ljungan virus has also been identified in several other species of voles, lemmings as well as yellow‐neck mouse (Apodemus), a hamster relative . Particular attention was paid when an epidemiological association between the periodic increase in number of lemmings and similar variation in incidence of T1D the following years, and antibodies to the virus were found to be quite common in diabetic children . It has been suggested that LV is involved in the pathogenesis of diabetes in BB‐rats .…”
Section: Introductionmentioning
confidence: 99%